ANALISIS PENGARUH LIKUIDITAS DAN PROFITABILITAS TERHADAP STRUKTUR MODAL PADA PERUSAHAAN FOOD AND BEVERAGE DI BURSA EFEK INDONESIA - Alamsyah, Agus Rahman (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2011)
This research aims to empirically examine the influence of liquidities and profitabilities to capital structure. Samples are 15 food and beverage sectors listed in Jakarta Stock Exchange (JSE) during 2006-2010. Multiple regressions are used to test hypotheses.  Financial ratios used in the liquidity ratio and profitability ratio, variable in this study are independent and dependent variables. The independent variable consist of Current Ratio (CRR), Cash Ratio (CAR), Quick-acid Test Ratio (QUR), Working Capital to Total Assets Ratio (WCR), Net Profit Margin (NPM), Rate of Return on Investment (ROI), and Rate of Return for the Owner-equity (ROE), and the dependent variable consist of Debt to Equity Ration (DER) and Debt to Assets Ratio (DAR). Results show that the liquidity ratio (cash ratio and working capital to total assets ratio) have negative impact on companies’ capital structure (debt to equity ratio and debt to assets ratio), but liquidity ratio is quick-acid test ratio has positive impact on companies’ capital structure (debt to equity ratio and debt to assets ratio). However profitability ratio (rate of return on investment) have negative impact on capital structure (debt to equity ratio and debt to assets ratio) to support the pecking order theory. The theory stated that the higher profitability the more retained returns so capital structure become lower.